NIOSH Hearing Loss Prevention Program for Mining - Peterson, Jeffrey Shawn; Azman, Amanda S. (Seminars in Hearing, 2023)
Noise-induced hearing loss (NIHL) continues to be a pervasive problem for the nation's workforce, particularly the nation's mining personnel. As one of the leading health and safety organizations in the world, the National Institute for Occupational Health and Safety (NIOSH) in Pittsburgh maintains a Hearing Loss Prevention Program (HLPP) to conduct research to reduce NIHL loss among the nation's miners. This document provides a brief overview of this HLPP, describing some of the research techniques involved in the development of engineering noise controls, methods for the development of administrative noise controls, and some of the products available to the public to protect the nation's workers hearing.
Keywords: NIOSH; hearing conservation; hearing loss prevention; hearing protection; mining; noise controls; NIHL